ANALISIS TINGKAT KEPUASAN TERHADAP KUALITAS PELAYANAN DAN FASILITAS SWALAYAN TOP 100 TEMBESI BATAM - Yan Mahesa Damanik (Universitas Putera Batam, 2019)
Batam City is a city located in the Riau Archipelago. Batam City is known as an industrial city, over time at this time Batam city is known as a tourist city and has several tourist attractions one of which is the beach. The beach in the city of Batam is widely used as a vacation spot by residents and tourists visiting the city of Batam. One of the beaches that become the target of visitors is the Mirota beach. Mirota Beach is a beach located in Sijantung Village, Galang Barelang Village, Galang Island, Batam, Riau Islands, Indonesia. To maintain and maintain the number of tourist visits an effort is needed to maintain the quality of service so that tourist satisfaction can be maintained and improved. The purpose of this study is to determine the level of satisfaction of visitors based on five aspects, namely tangible, assurance, empathy, reliability and responsiveness by taking a sample of 130 samples. The results of the study of 130 respondents were for the servqual score, namely the average value of the gab for each dimension on the mirota beach was tangible (-0,553), assurance (-0,529), empathy namely (-0,521), reliability (-0,581) and responsiveness (- 0.585). based on the calculation of servqual scores, the results of gab calculations for the five dimensions are the difference between reality and expectations> -1, which means good, while for quality (Q) each dimension is tangible 0.854, assurance 0.865, empathy is 0.867, reliability 0.852 and responsiveness 0.847. based on the calculation of the value of quality (Q) for the five dimensions that is close to 1 which means good.